2014
DOI: 10.1016/j.jstrokecerebrovasdis.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Poststroke Cognition, Baseline Factors, and Functional Outcome: Data from “Efficacy of Nitric Oxide in Stroke” Trial

Abstract: In previously independent individuals, cognitive impairment was common 3 months after stroke and related to increasing age, stroke severity, hypertension, atrial fibrillation, and cerebral atrophy on brain scanning. Cognition was related to dependency, disability, low mood, and quality of life. Hence, treatment directed toward reducing dependency might also reduce cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
1
41
0
3
Order By: Relevance
“…This is consistent with previous studies that have shown that left hemispheric stroke was an independent predictor of cognitive outcome at 3 months post stroke. 1,29,31,35 The left-sided predominance is not only driven by language deficit but may also be explained by the close relation between language and complex cognitive functions. 29,36 This is supported by our analysis on a subscore in which the most language-dependent items have been removed and which confirmed the improvement of the prediction after adding stroke location as variable.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies that have shown that left hemispheric stroke was an independent predictor of cognitive outcome at 3 months post stroke. 1,29,31,35 The left-sided predominance is not only driven by language deficit but may also be explained by the close relation between language and complex cognitive functions. 29,36 This is supported by our analysis on a subscore in which the most language-dependent items have been removed and which confirmed the improvement of the prediction after adding stroke location as variable.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is the second most common cause of acquired cognitive impairment, which predisposes patients toward institutionalization, disability, increased mortality, and poorer quality of life 1, 2, 3. With an aging population and a decline in mortality after stroke,4 the rates of poststroke cognitive impairment will increase.…”
Section: Introductionmentioning
confidence: 99%
“…C ognitive impairment after stroke is associated with depression and worse quality of life, 1 and previous stroke is associated with future risk of dementia. 2,3 Poststroke cognitive decline has been linked to advanced age, premorbid dementia, atrial fibrillation, white matter disease, hippocampal volume, and evidence of lacunar infarcts.…”
mentioning
confidence: 99%